Obyczaj zaręczyn i jego rola w procesie konstruowania małżeństwa - Przybył, Iwona (Wydawnictwo Naukowe UAM, 2008)
The aim of this article concentrates on the significance of betrothal and formal engagement in the process of building the marital partnership. The author tries to present the transformation of betrothal practices from the Middle Ages to present days. This paper is based on literature and the results of the author's study carried out in 2007. Earlier, engagement as the ritual of passage was a period for evaluating the relationship, learning to become more effective partners. Today all functions of engagement was redefined and caused to the traditional ceremony only.
The custom of the engagement and its role in the process of constructing marriage